The Influence of Work Performance and Discipline on Civil Servant Career Improvement at Marine Corps Command Headquarters - Mujiyati Mujiyati; Enjang Sudarman; Sukiman Sukiman (Dinasti International Journal of Management Science, 2026)
The research objectives are as follows: To determine the influence of work performance on career advancement of Civil Servants, To determine the influence of discipline on employee career development and To determine the influence of work performance and discipline on the career advancement of Civil Servants at the Marine Corps Command Headquarters. The calculated t value for the variable Work Performance (X1) is 2.831, while the t table value for N = 93 is 1.985. So 2.831 > 1. 98 5 , then Ho is rejected and Ha is accepted, it can be stated that Work Performance (X1) has a significant effect on Employee Career Improvement (Y), the calculated t value for the Discipline variable (X2) is 9. 877, while the t table value for N = 93 is 1. 98 5. So 9. 877 > 1. 98 5 , then Ho is rejected and Ha is accepted, it can be stated that Discipline (X2) has a significant effect on Employee Career Improvement (Y). ANOVA test or calculated f obtained a calculated f value of 450. 520 which is greater than the table f value for N = 93 of 2.70 or 450. 520 > 2.70 with a significance level of 0.000 because 0.000 < 0.05, it can be said that the Work Performance variable (X1) and the Discipline variable (X2) together have an effect on the Employee Career Development variable (Y).